Utility of 18F-FDG PET/CT in the assessment of lymphoepithelioma-like carcinoma. Issue 5 (May 2016) - Chan, Hiu Yan; Tsoi, Adelina; Wong, Maria Pik; Ho, James C.M.; Lee, Elaine Yuen Phin
Abstract : Lymphoepithelioma-like carcinoma (LELC) is a rare Epstein–Barr virus (EBV)-related disease, which commonly originates from the lung and is associated with more favourable treatment outcomes compared with other non-LELC thoracic carcinomas. Radiological assessment utilizing fluorine-18 fluorodeoxyglucose PET combined with computed tomography ( 18 F-FDG PET/CT) is important for initial disease staging to tailor the treatment strategy, evaluation of treatment response and detection of disease recurrence. The aim of this article was to highlight the utility of 18 F-FDG PET/CT in different stages of disease evaluation of LELC. We reviewed seven patients with histologically proven LELC who underwent 18 F-FDG PET/CT for disease evaluation. We described the 18 F-FDG-avidity of LELC (ranged from maximum standardized uptake value 7.6 to maximum standardized uptake value 14.5 in our series) and highlighted the clinical values of 18 F-FDG PET/CT in different stages of disease evaluation. 18 F-FDG PET/CT enables accurate evaluation of the primary tumour, its relationship with the surrounding structures and accurate staging. It is also useful in treatment response assessment to monitor the efficacy of the treatment and to decide upon treatment strategy. Given the 18 F-FDG-avidity of LELC, 18 F-FDG PET/CT is advantageous in detecting tumour recurrence of LELC. LELC is a rare disease entity associated with EBV and is more prevalent in Asia, where EBV is endemic. LELC is an 18 F-FDG-avid tumour. Although the features on 18 F-FDG PET/CT are not specific, 18 F-FDG PET/CT provides valuable information for disease management of LELC.